Pharmacokinetic drug‐drug interactions of tyrosine kinase inhibitors: A focus on cytochrome P450, transporters, and acid suppression therapy. Issue 3 (7th December 2016) - Gay, Caroline; Toulet, Delphine; Le Corre, Pascal
Abstract: The extensive use of tyrosine kinase inhibitors (TKI's) in hematology and oncology has shown that these drugs have a significant potential for drug‐drug interactions. Since these drugs have a rather low therapeutic window, some drug interactions are of particular clinical relevance either on drug toxicity or on patient's response. Significant interactions occur with concomitant use of acid‐suppressive therapy leading to a decreased oral bioavailability. However, such interactions are drug dependent according to their solubility pattern and to the duration of action of acid‐suppressive therapy, which is coprescribed. Significant interactions occur by inhibition or induction of CYP450 3A4 which is the main metabolic pathway of TKIs. However, minor metabolic pathways should also be paid attention to. Interactions involving efflux and influx transporters should also be considered occurring for some TKIs. Genetic polymorphism in drug metabolism as well as in drug transport is a factor of variability in drug exposure, which could modulate the magnitude of drug‐drug interactions (DDIs). It should be noticed that TKIs can also be at the origin of drug interactions by altering the pharmacokinetics of coprescribed drugs. Since cancer patients are given many drugs either for supportive care or for the treatment of drug toxicity, and to the fact that the oldest patients are polymedicated, a clear understanding of DDIs with TKIs is of interest. The objectives of this review are to provide an overview of the mechanisms of DDIs with TKIs and to provide to physicians and pharmacists recommendations to manage these DDIs in their clinical practice.